Finding a new test method for Inlay carpets instead of taxi tests - Kulkarni, Aniket; Budke, Tejas (My University, 2026)
This thesis focuses on developing a new and faster test method to evaluate wear in automotive inlay carpets, as an alternative to long taxi tests. Currently, the industry uses taxi based testing, where carpets are used in real taxis for about 1.5 years. However, this method has many limitations. The results depend on how different drivers use the car, as well as environmental conditions such as dirt, water, salt and stones. Because of this, the results are not consistent. In addition, standard laboratory tests like Taber and Martindale do not properly represent real foot movement of driving conditions. To solve this problem, a structured product development approach was used. This included reviewing research papers, studying existing patents and conducting user studies. A detailed user study was carried out with drivers of different percentile and driving habits. This helped to identify key types of foot movements, such as pivoting, sliding forward and backward, side movements and pedal pressing. These findings were then used to define requirements and develop different design concepts. Based on this, a proof-of-concept (POC) test rig was developed. The setup was designed to simulate real life foot movements, applied loads and environmental conditions like dirt and stones. Tests were carried out on different carpet materials, including Polyamide (PA) and Polyester (PES). The results show that the new method is able to reproduce some wear patterns, but they are not exactly the same as the taxi tested carpets. Overall, this study shows that including realistic human foot movement in testing improves the accuracy compared to existing test methods, but more modification and testing are required before it can be used as an industry standard.
Keywords: Inlay carpets; Taxi tests; Proof of concept (POC); Environmental conditions; Wear patterns